2016
DOI: 10.1590/2317-1545v38n4165265
|View full text |Cite
|
Sign up to set email alerts
|

Germination and initial development of Brachiaria brizantha and Brachiaria decumbens on exposure to cadmium, lead and copper

Abstract: -The objective was to evaluate the germination and initial development of three cultivars of Brachiaria brizantha and Brachiaria decumbens in the presence of trace elements of Cd, Pb and Cu and quantify the Cd and Cu contents in plant tissue of these species. First, seed germination occurred in towel paper containing cadmium, lead, copper and the control. We calculated the percentage of germination, germination speed index, vigor index and seedling length. Later, the seeds were germinated in soil pots contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…The results of this study corroborate Al-Qurainy (2010), who verified that in Eruca sativa root length decreased 28% and stem length decreased 44% for 50 mg L-1 of Cd. Also, Borges et al (2016) observed a reduction in root length of 2.5 and 1.0 cm in Brachiaria brizantha and B. decumbens when exposed to 180 mg L-1 of this metal. Similarly, Grigoraş and Stratu (2015) concluded that the Cd concentrations used (1.10; 1.6 and 2 mg L-1) did not affect seed germination, but negatively influenced seedling growth (especially the lengthening of the root) of Dianthus barbatus L. and D. chinensis L. According to these authors, the effect of the seedling growth delay can be attributed to metabolic and physiological disturbances caused by the Cd concentrations used in the treatments.…”
Section: Degrees Of Freedommentioning
confidence: 83%
See 1 more Smart Citation
“…The results of this study corroborate Al-Qurainy (2010), who verified that in Eruca sativa root length decreased 28% and stem length decreased 44% for 50 mg L-1 of Cd. Also, Borges et al (2016) observed a reduction in root length of 2.5 and 1.0 cm in Brachiaria brizantha and B. decumbens when exposed to 180 mg L-1 of this metal. Similarly, Grigoraş and Stratu (2015) concluded that the Cd concentrations used (1.10; 1.6 and 2 mg L-1) did not affect seed germination, but negatively influenced seedling growth (especially the lengthening of the root) of Dianthus barbatus L. and D. chinensis L. According to these authors, the effect of the seedling growth delay can be attributed to metabolic and physiological disturbances caused by the Cd concentrations used in the treatments.…”
Section: Degrees Of Freedommentioning
confidence: 83%
“…The main symptoms of toxicity are the following: inhibition of seed germination; disturbance of plant metabolic activities; reduction in the root system and stem; changes in the structure of chloroplasts; inhibition of photosynthesis; reduction of plant biomass; lipid peroxidation; decrease in respiration rate and growth; inhibition of the action of enzymes; reduction in cell division; and interference in cellular membrane permeability, which reduces the ability to absorb and transport water and essential elements (e.g., Ca, Mg and K) inside the plant, reducing tolerance to stress (Kabata-Pendias, 2010;Rahoui, Chaoui, & El Ferjani, 2010;Gill, Hasanuzzaman, Nahar, Macovei, & Tuteja, 2013;Chen et al, 2014). Studies of plant development under different Cd contamination levels have been conducted with the common bean (Santos, Fagan, Teixeira, Soares, Reis, & Corrêia, 2013), Jatropha curcas (Chaves & Souza, 2014), wheat (Ahmad, Akhtar, Zahir, & Jamil, 2012;Guilherme, Oliveira, & Silva, 2015), leaf mustard -Brassica juncea (Augusto et al, 2014;Alfiya & Dheera, 2015), crambe (Hu et al, 2015), Brachiaria brizantha and B. decumbens (Borges, D'avila, Campos, Coelho, Miquelluti, & Galvan, 2016), wheat and beans (El Rasafi, Nouri, Bouda, & Haddioui, 2016), chickpeas (Ahmad, Abdel-Latef, Abd-Allah, Hashem, Sarwat, Anjum, & Gucel, 2016), and basil -Ocimum basilicum - (Gharebaghi, Haghighi, & Arouiee, 2017), among others. However, no studies were found that evaluated the toxic effects of Cd on the seed germination of chia.…”
Section: Introductionmentioning
confidence: 99%
“…Para as variáveis IVG e RA ocorreu apenas efeito de dose de Cu, sendo que, a presença de Cu resultou em redução do IVG em dez vezes e inibiu a emissão de raiz (Tabela 3). As espécies de gramíneas estudadas por BORGES et al (2016) não apresentaram inibição de emissão de raiz, o que sugere, que as espécies avaliadas no presente estudo são menos tolerantes ao Cu.…”
Section: Dose (Mg Lunclassified
“…) (BORGES et al 2016). O efeito do Pb na germinação e desenvolvimento das plântulas das espécies aveia preta (Avena stringosa) e nabo forrageiro (Raphanus sativus) foi avaliado por BORGES et al (2019).…”
Section: Dose (Mg Lunclassified
See 1 more Smart Citation